Spontaneous Intraperitoneal Rupture of Bladder Diverticulum: A Rare Cause of Peritonitis - Ahmed Ibrahimi; Adil Kallat; Idriss Ziani; Hachem El Sayegh; Lounis Benslimane; Yassine Nouini (Case Reports in Urology)
Spontaneous rupture of acquired bladder diverticulum in an adult patient is an extremely rare pathological entity with only 15 cases reported in the available literature. Etiologies are dominated by bladder outlet obstruction, represented mainly by benign prostatic hypertrophy (BPH) in elderly men. Clinical presentation is nonspecific, leading to delayed diagnosis and treatment. Surgical management is the standard approach for intraperitoneal rupture of bladder diverticulum. The prognosis depends on the earliness of treatment, associated comorbidity, and the nature of underlying diseases. Herein, we report a rare case of a 65-year-old male patient, who presented a spontaneous rupture of a large acquired bladder diverticulum, secondary to acute urinary retention complicating benign prostatic hypertrophy. The diagnosis was suspected in the presence of generalized peritonitis associated with lower urinary tract symptoms (LUTS) and was confirmed accurately and promptly by a computed tomography (CT) of the abdomen and pelvis. The patient underwent a successful surgical excision of the diverticulum and bladder repair without delay. The postoperative course was uneventful, and he was discharged from the hospital without any complication.